Female genital tract microbiota affecting the risk of preterm birth: What do we know so far? A review. (February 2020) - Tsonis, O.; Gkrozou, F.; Harrison, E.; Stefanidis, K.; Vrachnis, N.; Paschopoulos, M.
Abstract: Spontaneous Preterm birth (SPTB) is a common obstetric complication affecting 12.9 million births worldwide and is the leading cause of neonatal morbidity and mortality. Disruption in the vaginal microbiota has an impact on the maternal immunological profile leading to SPTBs. Scientists have struggled to link maternal infectious agents with the dysregulation of the maternal immune response in cases of SPTBs. Throughout the last decade, important findings regarding the role of microbiota and its genome, the so-called microbiome, have linked alterations within the population of the microorganisms in our bodies with changes in nutrition, immunity, behaviour and diseases. In this review, evidence regarding the female genital tract microbiota and microbiome has been examined to help further our understanding of its role in disrupting the maternal immune system resulting in spontaneous preterm birth.